Association of Treatment and a 3-D image follow-up on a Recurrent Keratocyst - Case Report - Thereza-Bussolaro, Claudine; Aburad, Arlindo; Pachêco-Pereira, Camila; Flores-Mir, Carlos (Journal of Oral Diagnosis, 2017)
Introduction: Accordingly to the latest edition of the World Health Organization (WHO) the previously known Keratocyst Odontogenic Tumour (KCOT) has now returned to the simple odontogenic cyst (OKC) classification. We present a case successfully treated by a combination of minimal-invasive approaches. Case Presentation: A large OKC was identified extending from tooth 3.8 through the condylar process in the mandible and staged surgical conservative approaches were performed. Total healing was achieved and followed-up over 8 years. The case was well documented via panoramic radiographs, CBCTs, and a 3D image tool illustrates the cortical bone destruction (before treatment) and the cortical bone healing after treatment. Discussion: Agreement regarding terminology and treatment of OKC has been reached. In this case, a complete healing of a recurrent OKC was achieved by decompression, enucleation, and blurring of the bone walls. Rigorous follow-up enriched by a 3D reconstruction imaging allows an educational view of the healing. Conclusion: This case suggests that a staged surgery approaches concurrent to rigorous patient follow-up could be a feasible alternative to extensive OKT treatment. And, reinforces the importance of collaboration between orthodontist, pathologist, OMS, and the patient have crucial importance in the conservative management of the lesion.